Transient Porphyrinemia in a Neonate: A Case Report. Issue 6 (30th August 2016) - Boer, Brooke; Tisack, Alison; Shwayder, Tor
Abstract: We describe a neonate with anemia, thrombocytopenia, and hyperbilirubinemia secondary to hemolytic disease of the newborn. After phototherapy for hyperbilirubinemia, the neonate developed a photodistributed eruption with high serum and urine porphyrin levels. This transient porphyrinemia resolved at 1 month.